Limites do protagonismo dos comitês de bacia na descentralização da política nacional de recursos hídricos: uma análise do comitê de bacia do Rio Paranaíba - Corrêa, Edwiges Conceição Carvalho (2016)
Among the themes that appear in the agenda of environmental policy, the water crisis, which affects a large part of the world, is an important item that arouses the interest of governments and several social, environmental and market segments. In the globalized world, public policies and modes of management of water resources can be seen as a strategic and geopolitical issue given the importance of water for productive processes and life itself. In Brazil, water is managed by the basin committee, an administrative unit that is different from the politicaladministrative division of the Federation as established by the Federal Constitution of 1988. This work aims at discussing and understanding the role of the Basin Committee of the Paranaíba River in the of creation and decision processes of policies for the management of water resources in the basin as an integration of the institutional arrangement as defined by Law 9.433/1997, which establishes the participation of the Public Power, users and the organized civil society as agents in the shared management of water resources in Brazil. The investigated problem has been synthesized into an open question: What is the political protagonism of the basin committees within the institutional arrangement of decentralization of the national policy on water resources? The work is grounded on the hypothesis that the role of political protagonist of the basin committees is secondary in the decentralized structure of management of water resources in Brazil. Multi-method quality research was chosen as it is an approach that does not constrain the researcher to any given specific method only, but it also allows a wider range of data collection. In the present study, upon the association of more than one method of qualitative research, the multi-method approach was configured in the use of more than one instrument of field research and in the performed analysis. The work seeks to analyze and understand the dynamics of the decision-making process adopted by the Paranaíba River Basin Committee, with reference to the decentralization format for the management of water resources adopted by Law 9433/1997 and by the National Policy and Water Resources.The Basin Committee of the Paranaíba River was created through a Presidential Decree on 16 July 2002 and installed in 2008. It occupies an area of 63.3% of the state of Goiás, 3.4% of Mato Grosso do Sul, 31.7% of Minas Gerais and 1.6% of the Federal District. It encompasses 197 municipalities and the Federal District4. The research analyzes the period between the installation of the Basin Committee of the Paranaíba River – namely the year 2008 – and the publishing of the Plan of Water Resources of the Basin, in 2014.